Improving Brand Image of Product Through Integrated Marketing Communications - Akbar, Mohammad Aldrin; Sutisna, Entis (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines and analyzes the effect of Integrated Marketing Communication (IMC), which consists of advertising, sales promotion, public relations, personal selling, and direct and online marketing, on the brand image of electronic television products. Research Design and Methodology: This study's population consists of 2,576 customers who use Panasonic brand televisions. The sample size was determined using the Slovin formula, resulting in 100 respondents selected from the Jayapura area. This research employs a quantitative method using primary data from questionnaires distributed to respondents. Data were analyzed through several stages, including descriptive statistical analysis, validity and reliability testing, and hypothesis testing using the coefficient of determination (R²), partial test (t-test), and simultaneous test (F-test). Findings and Discussion: The results of this study indicate that advertising, sales promotion, public relations, personal selling, and direct and online marketing each have a positive and significant influence on the brand image of Panasonic television products. Among these variables, sales promotion is the most dominant factor influencing brand image. Implications: These findings suggest that companies should enhance their sales promotion strategies while strengthening other communication components to build a strong and competitive brand image in the electronics market.